PENGARUH CONTENT MARKETING TERHADAP COSTUMER ENGAGEMENT (STUDI KASUS PADA KONSUMEN MARKETPLACE SHOOPE DI KOTA BIMA) - Ismunandar Ismunandar; Nuir Khusnul Hamidah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to analyze and determine the influence of content marketing on customer engagement (Case study of shopee users in Bima City). This type of research is associative using quantitative data. The population in this research is all Shoppe users in Bima City using a research sample of 50 consumers using an accidental sampling technique. Data collection techniques include observation, interviews, questionnaires, documentation. Data analysis techniques use validity tests, reliability tests, simple linear regression tests, correlation coefficient tests, coefficient of determination, t tests with the help of SPSS version 26 for Windows. The research results show that there is an influence of content marketing on customer engagement (Case study of shopee consumers in Bima City.